Patrimonio Alimentario y Gastronómico del cantón Saquisilí. - Ullcu Telinchano, María Alejandra (2022)
The depreciation of culture, which is causing the loss of some customs and ancestral traditions of the native peoples, for which a research project has been conducted with the purpose of identifying the food and gastronomic heritage of the canton Saquisili as a means of dissemination of cultural diversity. The research carried out had a qualitative approach because it allows interpreting reality and at the same time collecting important data in order to obtain results. In the first objective, the analytical-synthetic method was used to compile the historical, social and cultural elements of the canton through primary and secondary sources such as books, magazines, documents, scientific articles obtaining the information, so that the canton Saquisili was a young town belonging to the province of Cotopaxi, It appears with the name of Chantillín, because in the past it was a swampy place, and from there the population was growing by hardworking and fighting people all over Ecuador and even internationally, since they have always been dedicated to agriculture, livestock and business in the fairs on Thursdays outdoors. In the second objective, the ethnographic method was applied with the techniques to inventory the food heritage, and the INPC cards for the inventory of the gastronomic heritage, resulting in 11 agricultural products produced in the canton, of which 5 agricultural products are considered as food heritage, by the ministry of culture 2013 and 1 was additionally included because it is frequently cultivated and 8 gastronomic dishes made with the food products harvested with knowledge and techniques transmitted. Finally, all the information collected was systematized in an academic article to disseminate to society.